Science Standard Four for primary school using multimedia application / Hazimi Zakaria - Zakaria, Hazimi (2005)
This research paper will discuss about E-Learning Multimedia covers science for primary school standard 4. This E-learning Multimedia application was developed because nowadays the technology growth quickly. For that reason, developer develop this multimedia software because think that everybody should take the chance to take up and improve our life by using technology method. The selected topic is science and it follows the syllabus and revised curriculum that was prepared for standard four pupils. This educational software divided into four sub topics or unit and only focus for topic 1 'Menyiasat Alam Kehidupan'. The main target users for this educational software are pupils and teachers standard four in primary school especially for them who not familiar with this kind of learning software. The contents are being presented in an interactive way consists of notes, exercises and games related to the learning process. Beside that, it also consists with impermanent notes and calendar. The entire layout screen being presented with animations, audio, images, text and graphical link to make the multimedia more interesting to learn. This multimedia package was easy to use because it is user friendly. Hopeftjily, with developing this multimedia software give a convenient for edutainment in the education.